Corrections to “Dynamic Security Analysis on Android: A Systematic Literature Review” - Thomas Sutter; Timo Kehrer; Marc Rennhard; Bernhard Tellenbach; Jacques Klein (IEEE Access)
Presents corrections to the paper, (Corrections to “Dynamic Security Analysis on Android: A Systematic Literature Review”).